Tecendo caminhos: o planejamento da coordenação pedagógica no encontro com o fazer docente - Falcão, Liana Kupas (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation examines the planning of pedagogical coordination in strengthening teaching practices and promoting integrated educational practices. Focusing on the planning and coordination between leadership and teachers, the study investigates how intentional and coordinated planning can address growing educational demands while fostering a collaborative and innovative teaching environment. It highlights that the lack of structured planning can lead to fragmented teaching practices disconnected from the institution's educational goals. In this context, the research aims to develop a pedagogical coordination plan that responds to new educational requirements and enhances teacher performance within the school, with five specific objectives: (1) to understand the practices of pedagogical coordination through documentary analysis, (2) to analyze communication and participation actions used by pedagogical coordination, (3) to identify how dialogue with teachers, integration, pedagogical support, and the development of educational practices are implemented, (4) to investigate the monitoring of teaching work and interventions by pedagogical coordination, and (5) to present a pedagogical coordination action plan with intentional and progressive actions developed throughout the academic year, aiming to strengthen support for the teaching staff. The theoretical framework covers topics such as the history of school supervision, educational management/school administration, educational management challenges, and planning. A qualitative methodology was employed, based on a case study, which includes documentary analysis, secondary data research, and semi-structured interviews. The state-of-the-art review reveals that this research aims to contribute to the field of educational management by highlighting the importance of participatory and planned pedagogical coordination. This approach fosters teaching practices aligned with contemporary needs and realities, enriching pedagogy with intentionality and cohesion.
Keywords: Gestão educacional; Coordenação pedagógica; Educação básica; Educational management; Pedagogical coordination; Basic education; ACCNPQ::Ciências Humanas::Educação